Technological profile of ranchers in the Pirajibu-Mirim river watershed - Nery, Liliane Moreira [UNESP]; Collins da Cunha e Silva, Darllan [UNESP]; Sabonaro, Débora Zumkeller (University Nove de Julho, 2022)
Objective: To analyze the technological profile of ranchers in a watershed located in Sorocaba-SP (Brazil) using technological and socioeconomic indicators. Method: Sorocaba city and São Paulo State census data, as well as interview data, were used in this study to verify the profile of ranchers in the watershed under study. Uniqueness/Significance: Even though different agricultural production systems have similarities; each farm has its limitations in available resources. In this sense, technologies must be implemented on these farms for their long-term maintenance. However, smallholder farmers usually hesitate to incorporate new technologies. Thus, public policies that support investment in human, technological, and infrastructural capital should be developed to ensure higher productivity, income generation, and competitiveness among producers. Results: Cattle ranchers in the study region lack access to infrastructure and agricultural training. Social contributions: Obtaining and making data available can improve the understanding of parameters that allow decision-making in public policies to improve the social, technological, and economic conditions of ranchers in the area under study.
Perfil tecnológico de los ganaderos de la cuenca hidrográfica del río Pirajibu-Mirim
Perfil tecnológico dos pecuaristas da bacia hidrográfica do rio Pirajibu-Mirim
Keywords: Infrastructure; Technology; Training